Validation of notch stress estimation schemes for low C–Mn steel. Issue 4 (7th February 2022) - Jena, Shreebanta Kumar; Arora, Punit; Gupta, Suneel K.; Chattopadhyay, Jayanta
Abstract: The present study is aimed at validation of notch stress/strain estimation schemes such as classical Neuber, Hoffmann–Seeger, and recently developed Ince–Glinka method for nuclear piping material (low C–Mn steel). The study has considered different constraints, loading conditions, and various hole sizes to accommodate strain gradient variations and equivalent peak strains. The notch stress field evaluated using these schemes is compared with corresponding stress using elastic–plastic finite element (FE) analyses. The comparisons have brought out that the Hoffmann–Seeger scheme results in reasonably accurate assessment of stress localization nearly for all constraint geometries, loadings, and strain gradients. However, the classical Neuber scheme is more suitable for low constraint geometries and intermediate constraint geometries, whereas it results in underestimation of maximum principal stress for high constraint geometries, thereby leading to overprediction of fatigue life. Further, the suitability of energy equivalence equations of Ince–Glinka model for individual stress components has been reviewed.